Zilbes intonāciju stabilitāte divu paaudžu laikā - Rūķe-Draviņa, Velta (Baltistica, 1978)
Stability of syllable intonation in two generationsThe purpose of this study is to investigate: 1) the retention of the Latvian language syllable intonation in the course of an individual's lifetime, 2) the possibility of transference of an intonation system from one generation to another in bilingual surroundings.This work analyzes three idiolects in the same family, namely, a Latvian-Swedish bilingual’s (born 1946, Stockholm) idiosyncracies of pronunciation in comparison to the language of his parents, who each represent the intonation system of their native region: the mother – Selian, the father – Southwestern-Kursa dialects.This investigation determines that an intonation system acquired in childhood and stabilized at grammar school age remains stable even later on in the life of the individual, and does not change even with prolonged contact with speakers of other intonation systems in the same family over a period of thirty years.If each of the parents has his own intonation system, and only one of them speaks with the intonations common to the literary language, then there is a high probability that the child will acquire the latter variant.In ideal balanced bilingual circumstances, a bilingual individual can learn genuine intonations in both languages, i.e. in this case in Swedish the phonological contrast between “accent 1” and ”accent 2”, but in Latvian, the contrast between the level tone and the non-level tone.
Keywords: akcentologija; priegaidės latvių kalboje; priegaidžių pastovumas; bilingvizmas